2023
DOI: 10.3390/met14010042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nb Content on the Microstructure and Impact Toughness of High-Strength Pipeline Steel

Jinxing Jiang,
Zhongde Zhang,
Kai Guo
et al.

Abstract: In this study, X80 pipeline steel is prepared with different Nb contents through the thermo-mechanically controlled rolling process. The effects of using two different Nb contents on the impact toughness and microstructure of the pipeline steel are examined using various experimental techniques. The results show that with the increase in Nb content, the transformation temperature Ar3 decreases, and the nucleation and growth of bainitic ferrite with lath features (LB) are promoted, while those of granular baini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These precipitates act as stress concentrators in the material and reduce the impact strength. Various studies have shown that large precipitates of Nb can have a negative impact on toughness, mainly [5,6,24,25]. These precipitates formed in the structure before aging.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…These precipitates act as stress concentrators in the material and reduce the impact strength. Various studies have shown that large precipitates of Nb can have a negative impact on toughness, mainly [5,6,24,25]. These precipitates formed in the structure before aging.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Considering the beneficial effect of large-angle grain boundaries on impact toughness, an appropriate amount of V is added in the composition design to make the experimental steel exhibit more stable impact toughness under the same conditions as much as possible. Jiang et al [24] conducted a study on the influence of different Nb contents on the microstructure evolution and impact behavior of M/A, and found that an increase in Nb content leads to an increase in the proportion of M/A components, and a decrease in the crack initiation energy. Further analysis revealed that an increase in the proportion of M/A components has a certain adverse effect on impact toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The toughening mechanism below the X100 level has been well studied. There, a good match of strength and toughness was achieved [8][9][10][11][12][13][14]. The contradiction between strengthening and toughening becomes more prominent when the steel grade reaches X100 [7,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%